Frameless Fractionated Stereotactic Radiosurgery for Vestibular Schwannomas: A Single-Institution Experience - Karam, Sana D.; Tai, Alexander; Strohl, Alexis; Steehler, Matthew K.; Rashid, Abdul; Gagnon, Gregory; Harter, K. William; Jay, Ann K.; Collins, Sean P.; Kim, Jeffrey H.; Jean, Walter (Frontiers in Oncology, 2013)
Objective: To examine tumor control, hearing preservation, and complication rates after frameless fractionated stereotactic radiosurgery (SRS) in patients with vestibular schwannomas (VS). Methods: Thirty-seven patients treated with fractionated SRS from 2002 to 2011 were retrospectively analyzed. Ninety-five percent were treated with 25 Gy in five fractions, targeting a median tumor volume of 1.03 cc (range 0.14–7.60). Results: With a median follow-up of 4.25 years (range, 15 months–9 years), no tumors required an additional treatment resulting in 100% tumor control rate. Radiographic control rate was 91% in 32 patients at a median follow-up of 3 years. Of the 14 patients with serviceable hearing and with audiograms, the hearing preservation rate was 78% at a median follow-up of 18 months. Twenty-six patients with serviceable hearing pretreatment, were evaluated by a phone survey with a hearing preservation rate of 73% at a 5 year median follow-up. There were two cases that developed both new increased trigeminal parasthesias and facial spasms but there were no cases of facial weakness. Patient had 96% of good to excellent satisfaction rate with the treatment at a median follow-up of 5 years. Conclusion: Frameless fractionated SRS treatment of VS results in good rate of tumor control. Hearing preservation rate and rates of cranial nerve toxicity are comparable to what is reported in the literature. Patients choose this modality because of its non-invasive nature and are generally very satisfied with their long term outcome.